Brazil - Youth at Risk in Brazil - World Bank (Washington, DC, 2012)
Brazilian young people are well on their way to becoming productive and contributing members of society. Three-quarters of young Brazilians surveyed responded that they are happy with themselves and with their lives. And they have the numbers to make substantial contributions to the present and future of their society -- 19 percent of the Brazilian population is aged 15 to 24 and Brazilian young people comprise one-third of the youth population of Latin America. This report is the first volume of a two-volume series. The second volume is a technical report that presents the statistical results in detail. This first volume summarizes the 100-page second volume. It gives a brief review of the report's empirical findings and of the correspondence to youth development policy and programming in Brazil.